Invasive disease potential of pneumococci before and after the 13-valent pneumococcal conjugate vaccine implementation in children. Issue 46 (17th November 2015) - Varon, Emmanuelle; Cohen, Robert; Béchet, Stéphane; Doit, Catherine; Levy, Corinne
Highlights: Before and after PCV13 implementation, the ST relationship between carriage and IPD was investigated. In children <2 years old, 569 IPD and 355 Sp isolated from 1212 healthy were compared. Before PCV13, 5 serotypes: 7F, 3, 1, 24F, and 19A had high invasive disease potential. After PCV13, only 2 serotypes: 24F and 12F had high invasive disease potential. Abstract: Background: Changes in serotype distribution have been induced after pneumococcal conjugate vaccines (PCV) implementation, and non-vaccine serotypes are now circulating. Among these latter serotypes, we aimed to distinguish those with high invasive disease potential before (2008–2009) and after PCV13 implementation (2012–2013). Methods: Invasive pneumococcal disease (IPD) serotypes isolated from children 6 to 24 months were compared with nasopharyngeal-colonizing serotypes in healthy children. To assess the invasive potential of a given serotype, odds ratios (ORs) were calculated. For each serotype, OR >1 indicated increased probability of association with IPD and OR <1 decreased probability. Results: In 2008/2009 and 2012/2013, 355 pneumococci were isolated from 1212 healthy children and from 569 IPD, including 166 meningitis, 114 pneumonia, and 289 other IPDs. In period 1, serotypes 7F, 3, 1, 24F, and 19A showed highly significant invasive disease potential whereas in period 2, only serotype 24F was associated with a significant high OR (6.6 [95% CI 2.6; 16.2]). Of note, for serotype 12F, OR could not be calculated because of no carrier recorded, however, if there had been a single 12F carrier, the OR would be among the highest, in period 2, 15.7 [95% 3.4; 73.0]). Only two serotypes appeared negatively associated with IPD, 11A and 23B in the period 2 as compared with nine in period 1. In the second period, pneumococcal penicillin non-susceptible isolates were mostly represented by serotypes 19A, 15A, 19F, 35B and 24F both in carriers and IPD. Only one strain was resistant to penicillin with MIC = 4 μg/ml (serotype 19A) during the first period. Conclusion: In children <2 years old, compared to the previous period, the number of serotypes having a high disease potential decreased after PCV13 implementation, only two non-vaccine serotypes, 24F and 12F, had high invasive disease potential.